Ralph Vaughan Williams and Adrian Boult - Simeone, Nigel 1956- (The Boydell Press, 2022)
From 1918 onwards, Boult became one of Vaughan Williams's most important interpreters, giving the world premieres of the Pastoral, Fourth and Sixth Symphonies, performing almost all his major works (not only at home but with some of the world's greatest orchestras), and working in close collaboration with the composer on major projects including the first complete recording of Vaughan Williams's symphonies. Boult continued to be the most devoted advocate of Vaughan Williams's music to the end of his long career.As this book shows, Boult's scores include numerous annotations derived from conversations and correspondence with Vaughan Williams and these provide important evidence of the composer's wishes including adjustments to orchestration, comments on interpretation, dynamics, phrasing and revisions to Vaughan Williams's notoriously unreliable metronome marks. The evidence of these scores is considered alongside the extensive correspondence between Vaughan Williams and Boult, Boult's private diaries and other relevant documents including contemporary press reports. The book includes three substantial supplements: a detailed description of Boult's marked scores, a comprehensive list of Boult's Vaughan Williams performances and a discography including surviving recordings of unpublished broadcasts. It will be indispensable reading for scholars and students of Vaughan Williams and historical conducting, Vaughan Williams enthusiasts and those interested in the history of recorded music
Keywords: Vaughan Williams, Ralph -- 1872-1958; Boult, Adrian -- 1889-1983; Geschichte; Vaughan Williams, Ralph / 1872-1958 / https://isni.org/isni/0000000108591472; Boult, Adrian / 1889-1983 / https://isni.org/isni/0000000110386101; Vaughan Williams, Ralph / 1872-1958 / Influence; Vaughan Williams, Ralph / 1872-1958 / Correspondence; Boult, Adrian / 1889-1983 / Correspondence; Conducting; Composition (Music); Boult, Adrian / 1889-1983; Vaughan Williams, Ralph / 1872-1958; Personal correspondence